2014
DOI: 10.1163/22134468-00002026
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Numerical Ability Affects Supra-Second Time Estimation

Abstract: It has been suggested that the human ability to process number and time both rely on common magnitude mechanisms, yet for time this commonality has mainly been investigated in the sub-second rather than longer time ranges. Here we examined whether number processing is associated with timing in time ranges greater than a second. Specifically, we tested long duration estimation abilities in adults with a developmental impairment in numerical processing (dyscalculia), reasoning that any such timing impairment co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…Based on this model, number and duration discrimination rely on a single magnitude system which operates in either the counting or the timing mode (Fetterman, 1993). From an experimental perspective, a number of behavioral (Alards-Tomalin, Walker, Kravetz, & Leboe-McGowan, 2016;Cappelletti, Freeman, & Butterworth, 2011;Cappelletti et al, 2009;Chun, Lee, Lee, & Cho, 2018;Dormal, Seron, & Pesenti, 2006;Gilaie-Dotan, Rees, Butterworth, & Cappelletti, 2014;Javadi & Aichelburg, 2012;Lambrechts, Walsh, & Van Wassenhove, 2013;Martin, Wiener, & Van Wassenhove, 2017;Tokita & Ishiguchi, 2011;Tsouli, Dumoulin, te Pas, & van der Smagt, 2019) and neuroimaging (Bueti & Walsh, 2009;Cappelletti et al, 2014;Castelli, Glaser, & Butterworth, 2006;Hayashi et al, 2013;Javadi, Brunec, Walsh, Penny, & Spiers, 2014) studies provide support for a partly shared processing system for numerosity and time, whereas other studies suggest that numerosity and time are independent and are processed by distinct mechanisms (Agrillo, Piffer, & Adriano, 2013;Agrillo, Ranpura, & Butterworth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this model, number and duration discrimination rely on a single magnitude system which operates in either the counting or the timing mode (Fetterman, 1993). From an experimental perspective, a number of behavioral (Alards-Tomalin, Walker, Kravetz, & Leboe-McGowan, 2016;Cappelletti, Freeman, & Butterworth, 2011;Cappelletti et al, 2009;Chun, Lee, Lee, & Cho, 2018;Dormal, Seron, & Pesenti, 2006;Gilaie-Dotan, Rees, Butterworth, & Cappelletti, 2014;Javadi & Aichelburg, 2012;Lambrechts, Walsh, & Van Wassenhove, 2013;Martin, Wiener, & Van Wassenhove, 2017;Tokita & Ishiguchi, 2011;Tsouli, Dumoulin, te Pas, & van der Smagt, 2019) and neuroimaging (Bueti & Walsh, 2009;Cappelletti et al, 2014;Castelli, Glaser, & Butterworth, 2006;Hayashi et al, 2013;Javadi, Brunec, Walsh, Penny, & Spiers, 2014) studies provide support for a partly shared processing system for numerosity and time, whereas other studies suggest that numerosity and time are independent and are processed by distinct mechanisms (Agrillo, Piffer, & Adriano, 2013;Agrillo, Ranpura, & Butterworth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This fixed criterion task (Gilaie-Dotan et al, 2011 , 2014 ) required participants to discriminate between two visually presented and a priori known duration intervals of 9 s and 9.9 s in a two alternative forced choice (2AFC) manner. Critically, the same paradigm also served for the non-temporal control experiment with a simple change of task (see Task 2 below and Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…These control tasks had an identical experimental paradigm apart from requiring participants to discriminate between colors instead of discriminating between intervals (i.e., change of task). These color perception controls tasks were inspired by Coull et al’s ( 2004 ) study, and are assumed to rely on color perception mechanisms that have been shown to dissociate from timing mechanisms both neurally and perceptually (Coull et al, 2004 ; Gilaie-Dotan et al, 2011 , 2014 ). As OCD is often accompanied by anxiety and depression (American Psychiatric Association, 2013 ), we also controlled for the levels of these variables using participants’ scores on a self-report scale Depression, Anxiety and Stress Scale (DASS; see “Materials and Methods” section).…”
Section: Introductionmentioning
confidence: 99%
“…The parents of all these children agreed to their children's participation in this study. All comparisons between BN's performance and that of the control group were according to established single case vs. group modified t-test comparisons (Crawford and Howell 1998, Crawford and Garthwaite 2002, Crawford et al 2009, Gilaie-Dotan et al 2009, Gilaie-Dotan et al 2011, Brooks et al 2012, Gilaie-Dotan et al 2013a, Gilaie-Dotan et al 2013c, Gilaie-Dotan et al 2014, Freud et al 2016, using the SINGLIMS software (http://homepages.abdn.ac.uk/j.crawford/pages/dept/SingleCaseMethodsComputerProgra ms.HTM).…”
Section: Controlsmentioning
confidence: 99%